Incidence, mechanisms, and severity of match-related collegiate men`s soccer injuries on fieldturf and natural grass surfaces: A 6-year prospective study - Meyers, M. C. (The American Journal of Sports Medicine, 2017)
Background: Numerous injuries have been attributed to playing on artificial turf. More recently, newer generations of artificial turf have been developed to duplicate the playing characteristics of natural grass. Although artificial turf has been deemed safer than natural grass in some studies, few long-term studies have been conducted comparing match-related collegiate soccer injuries between the 2 playing surfaces. Hypothesis: Collegiate male soccer athletes do not experience any difference in the incidence, mechanisms, or severity of match-related injuries between FieldTurf and natural grass. Study Design: Cohort study; Level of evidence, 2. Methods: Male soccer athletes from 11 universities were evaluated over 6 seasons. Demographic features and predictors included player position, cleat design, player weight, turf age, and environmental factors. Outcomes of interest included injury incidence, injury category, time loss, injury mechanism and situation, type of injury, injury grade and anatomic location, injury severity, head and lower extremity trauma, and elective medical procedures. All match-related injuries were evaluated by the attending head athletic trainer and team physicians on site and subsequently in the physician`s office when further follow-up and treatment were deemed necessary. In sum, 765 collegiate games were evaluated for match-related soccer injuries sustained on FieldTurf or natural grass during 6 seasons. Results: Overall, 380 team games (49.7%) were played on FieldTurf versus 385 team games (50.3%) played on natural grass. A total of 722 injuries were documented, with 268 (37.1%) occurring on FieldTurf and 454 (62.9%) on natural grass. Multivariate analysis per 10 team games indicated a significant playing surface effect: F2,720 = 7.260, P = .001. A significantly lower total injury incidence rate (IIR) of 7.1 (95% CI, 6.6-7.5) versus 11.8 (95% CI, 11.3-12.2; P < .0001) and lower rate of substantial injuries, 0.7 (95% CI, 0.5-1.0) versus 1.9 (95% CI, 1.5-2.3; P < .03), were documented on FieldTurf versus natural grass, respectively. Analyses also indicated significantly less trauma on FieldTurf when comparing injury category, time loss, player position, injury mechanism and situation, injuries under various environmental conditions, cleat design, turf age, anatomic location, and elective medical procedures. No significant difference (F11,710 = 0.822, P = .618) between surfaces by knee injury was observed, with the majority of knee injuries involving patellar tendinopathies/syndromes followed by medial collateral ligament injuries on both surfaces. Conclusion: Although similarities existed between FieldTurf and natural grass during competitive match play, FieldTurf is, in many cases, safer than natural grass when comparing injuries in collegiate men`s soccer. The findings of this study, however, may not be generalizable to other levels of competition or to other artificial surfaces.